GENERATION Z'S JOB APPLICATION INTENTION: THE ROLE OF E-RECRUITMENT AND SOCIAL MEDIA AT PT VICTORY INTERNATIONAL FUTURES - Retha Divi Narinta; Alfiandi Imam Mawardi (Journal Economics Technology And Entrepreneur, 2025)
This study examines how e-recruitment and social media affect job application intention within Generation Z at PT Victory International Futures, Ciputra World Branch. PT Victory International Futures is a service company focusing on investment, forex, indices, and commodities, which has demonstrated that electronic recruitment through its website and social media platforms such as TikTok has successfully attracted young candidates and resulting in increased job application volumes. However, quantitative measurement is essential to determine the magnitude of these effects amid fierce competition in the financial industry. The quantitative approach utilized Google Forms for data collection from 96 respondents selected via Slovin's formula from @victory_ciputraworld TikTok followers. Statistical analysis utilized SEM-PLS software. Results demonstrate that e-recruitment and social media significantly and positively impact job application intention among Generation Z at PT Victory International Futures.